Characterization and spatial georeferencing of the physical properties of Eutric Fluvisols soils for agricultural use in the "La María" Experimental Farm in the Mocache Canton (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
This work was carried out in the Experimental Farm "La María" ofthe State Technical University of Quevedo (UTEQ) with theobjective of characterizing and georeferencing the physicalproperties of the Eutric Fluvisols soils for agricultural use in thefarm "La María". Where there is a lack of knowledge of the physicalcharacteristics, inadequate management and use of soils beingnecessary the use of technologies such as geographic informationsystems (GIS) that allow storing, analyzing and managing activitiesof the different sites of agricultural interest. This research wasconducted from June to October 2018, using a completelyrandomized design (CRD) with 20 treatments considered byhorizons and surfaces in 3 replications. The data were analyzed inthe statistical program InfoStat free version (VL), and subjected toTukey's test at 95% probability. These results were plotted on ageoreferenced map in a GIS (ARGIS) (VL), WGS 1984 UTM Zone 17Scoordinate system. The soils of the "La María" farm had an averagebulk density of 1.18 g/cm3 and real density of 2.24 g/cm3. Therewas a pore space percentage of 46%, average moisture percentageof 41%, and soil aggregate size of 4.28 mm. In the texture analysis,85% of the soils of the farm have a loamy soil texture.